Consumer Preferences for Seoca Nugget: A Plant-Based Meat Innovation in Sustainable Food Markets - Galih Punta Indra Nugraha; Restin Meilina (PT. Anagata Sembagi Education, 2025)
Nuggets are one of the protein ready-to-eat food products that are now trending and can be accepted by the public because they are more practical, economical, and easy to consume. One form of food processing that can increase the nutritional value of processed products is vegetable nuggets. Vegetable nuggets are healthy, high in fiber, and come from nature. Vegetables can be processed goods that not only increase their selling value but also fall into the category of ASUH products (safe, healthy, intact, and hygienic). This research analyze consumer preferences in purchasing decisions for Seoca Nugget products, an alternative to vegetable protein nuggets that utilize cassava, soybeans, and mushrooms as meat substitutes. The main focus of the study is to understand how product attributes such as packaging, price, size, nutritional information, brand, and ease of obtaining influence consumer decisions in purchasing Seoca Nugget. In addition, this study also identifies the priority order of attributes that are the basis for purchasing, the most dominant attributes in consumer preferences, and the main reasons consumers choose this product. The method used was qualitative descriptive through in-depth interviews with 4 informants. The results of the study show that the attributes of packaging, size, nutritional information and ease of obtaining are very important preferences for consumers to decide to buy Seoca. While price, and brand are not so important preferences in buying Seoca. Consumers' preference to buy Seoca as a protein alternative is getting stronger because the nutritional information obtained shows that the vegetable protein content in this product is almost equivalent to the protein content in chicken nuggets.